Integration of Huyula Cultural Values in Group Counseling Services: A Local Wisdom-Based Model for Gender Awareness among High School Students - Siregar, Ilham Khairi; Korompot, Salim; Pautina, Mohamad Rizal; Sari, Permata; Putri, Sefni Rama; Tuasikal, Jumadi Mori Salam; Alhasni, Jahra (Jurnal SOMASI (Sosial Humaniora Komunikasi), 2025)
Gender inequality in secondary schools remains a serious problem characterized by strong gender role stereotypes and low social participation of female students. In Gorontalo Province, this condition is reinforced by patriarchal cultural constructs that are internalized in educational practices and have not been addressed contextually through school services. This study offers a solution through the integration of local wisdom values (huyula) into group counseling services as a culture-based approach to increase students' gender awareness. The study aims to analyze the initial conditions of gender awareness, describe the implementation of huyula-based group counseling, and evaluate changes in students' understanding and attitudes toward gender equality. The study uses a qualitative approach with a case study method in three high schools in Gorontalo Province. Data were collected through observation, in-depth interviews, focus group discussions, and documentation, then analyzed thematically. The results showed that the integration of the values of mutual cooperation, equal responsibility, and mutual respect in group counseling encouraged a shift in students' perspectives toward a more equal view of gender roles. These findings emphasize the importance of counseling services based on local wisdom as a contextual solution in strengthening gender awareness in schools.